Analysis Of Tapered Finline In Power Combiner For Wideband Application - Abd Aziz, Mohamad Zoinol Abidin; Nur Shaheera Alia, Sadick Ali; Ahmad, Badrul Hisham; Mohd Azlishah, Othman; Hamzah Asyrani, Sulaiman (Penerbit UTM Press, 2016)
Tapered finline or slotline array has used in Vivaldi antenna design to produce Ultra-wideband (UWB). This paper focuses to design and analysis the structural of tapered finline in order to achieved wideband in rectangular waveguide power combiner at frequency 0.5 GHz to 6 GHz. There are three main parameters are studying in this paper which are of length of radiation region exponential coefficient at curves of radiation and exponential coefficient at curves of directivity. The design of tapered finline in power combiner is simulated using CST Microwave Studio Software. The simulation process is based on the input return loss at port 1 (S11), input return loss at port 2 (S22), isolation (S21) and insertion loss (S12). By studying the effect of the parameter on the design structure, it can be ensure that the tapered finline structures are suitable in wideband design.